2016
DOI: 10.3390/membranes6020033
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Bioreactor (MBR) Technology for Wastewater Treatment and Reclamation: Membrane Fouling

Abstract: The membrane bioreactor (MBR) has emerged as an efficient compact technology for municipal and industrial wastewater treatment. The major drawback impeding wider application of MBRs is membrane fouling, which significantly reduces membrane performance and lifespan, resulting in a significant increase in maintenance and operating costs. Finding sustainable membrane fouling mitigation strategies in MBRs has been one of the main concerns over the last two decades. This paper provides an overview of membrane fouli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(157 citation statements)
references
References 178 publications
3
151
0
3
Order By: Relevance
“…With smaller pores, large particles rapidly form a top layer on the membrane and collect the smaller particles. Large particles can then be removed easily by a simple hydraulic cleaning [76]. In this respect, pristine PVDF membrane with a larger diameter and pore size of 1.49 μm is expected to experience more pore blocking than the PVDF-2% Ag and PVDF-2% Ag-GO composite membranes with smaller diameters and respective pore sizes of 0.69 and 0.63 μm.…”
Section: Water Permeability and Antifouling Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…With smaller pores, large particles rapidly form a top layer on the membrane and collect the smaller particles. Large particles can then be removed easily by a simple hydraulic cleaning [76]. In this respect, pristine PVDF membrane with a larger diameter and pore size of 1.49 μm is expected to experience more pore blocking than the PVDF-2% Ag and PVDF-2% Ag-GO composite membranes with smaller diameters and respective pore sizes of 0.69 and 0.63 μm.…”
Section: Water Permeability and Antifouling Behaviormentioning
confidence: 99%
“…They reported that the membranes can remove micro-particles in the range of 5-10 μm effectively during filtration. Generally, pore blocking mechanism tends to increase with increasing membrane pore size [76]. It is easier for fine particles (smaller than the membrane pore size) to enter the membrane pores and get trapped in them, resulting in pore blocking.…”
Section: Water Permeability and Antifouling Behaviormentioning
confidence: 99%
“…Fouling brings about reduced flux or increased applied pressure which will results in the decrease of the membrane lifetime. Along these lines, lessening of the membrane fouling is one of the primary points of scientists ,. Since the performance of membrane filtration depends greatly on the membrane fouling then great attention was devoted on modification and improvement of antifouling ability of membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane bioreactor technology (MBRs) have been used for treatment and reclamation of municipal and industrial wastewater [27]. Membrane processes have a great many unique advantages, including easy maintenance, stationary parts with compact modular construction, low chemical sludge effluent, and excellent separation efficiency.…”
Section: Membrane Filtrationmentioning
confidence: 99%